Environmental accounting: an analysis on the transformation of environmental impacts in sustainable and socioeconomic improvement, in the Supply Center Hortifrutigranjeiro – Ceasa MA - Araujo, Lauralice Ferreira; Sillva, Maria Raimunda Chagas; Mattos, Delmo Silva (Ciência e Natura, 2018)
This objective of this article is to analyze the, transformation of environmental impacts into some amount of sustainable and socioeconomic improvements within the Supply Center Hortifrutigranjeiro – CEASA MA from 2016 to 2017. Using data processing, the analytic approach of action research, described in comparison to an exploratory analysis of the field to meet the guidelines of the national policy on solid waste. The results showed that food waste still lacks proper control and treatment, and generates express environmental and accounting liabilities, given that some of it is are thrown into enclosure, which is difficult for needy families to access, what is not segregated, turns to slurry, damaging the soil and the nearby water table; the remainder of the waste is routed to landfill, sites, which generates transportion costs. Given, this context, it was to concluded that the applicable public policies the state and local management will need to be integrated, these should aim primarily at raising environmental awareness of the importance of waste management, in the purpose of Converting soil degradation and accounting for damage to a sustainable form of, development thereby emphasizing environmental preservation and combating social inequality.